2002
DOI: 10.1007/s00424-002-0869-y
|View full text |Cite
|
Sign up to set email alerts
|

MgATP and phosphoinositides activate Na + /Ca 2+ exchange in bovine brain vesicles. Comparison with other Na + /Ca 2+ exchangers

Abstract: We investigated the metabolic modulation of the Na(+)/Ca(2+) exchanger in membrane vesicles obtained from bovine brain. The Na(+)/Ca(2+) exchanger was activated by MgATP with a K(0.5) of 336 micro M. Unlike the squid nerve Na(+)/Ca(2+) exchanger, this effect required no cytosolic component. Also, stimulation is the same in vesicles prepared and/or assayed at the ionic strength found in mammals (160 mM) or marine animals (300 mM). Other differences between squid and bovine nerve are that the bovine brain Na(+)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In dialyzed squid axons, where the four exchange modes are all stimulated by MgATP, stimulation is increased by intracellular vanadate (K 1/2 ϳ10 M) and millimolar concentrations of inorganic phosphate and p-nitrophenylphosphate (75). The mammalian heart exchanger in native cells, or even expressed in heterologous cells, under patch-clamp conditions is stimulated by MgATP; mammalian heart sarcolemmal or brain vesicles require the addition of 100 -500 M vanadate (26,27). Upon removal of ATP, in the presence of Mg 2ϩ , upregulation of the exchangers is lost (93).…”
Section: C) Basic Characteristics Of Atp-regulated Transport Sys-temsmentioning
confidence: 99%
See 2 more Smart Citations
“…In dialyzed squid axons, where the four exchange modes are all stimulated by MgATP, stimulation is increased by intracellular vanadate (K 1/2 ϳ10 M) and millimolar concentrations of inorganic phosphate and p-nitrophenylphosphate (75). The mammalian heart exchanger in native cells, or even expressed in heterologous cells, under patch-clamp conditions is stimulated by MgATP; mammalian heart sarcolemmal or brain vesicles require the addition of 100 -500 M vanadate (26,27). Upon removal of ATP, in the presence of Mg 2ϩ , upregulation of the exchangers is lost (93).…”
Section: C) Basic Characteristics Of Atp-regulated Transport Sys-temsmentioning
confidence: 99%
“…Incidentally, in bovine brain membrane vesicles, MgATP stimulation is related to PtdIns(4,5)P 2 , but ATP␥S is no more than one-third as effective. In this case, however, a mixture of exchanger isoforms cannot be ruled out as a possible explanation (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a way, this result marks another difference with the mammalian cardiac and nerve exchangers. In the membrane vesicles from the mammalian heart 6 and brain, 8 MgATP upregulation requires the simultaneous presence of vanadate, whereas in dialyzed squid axons 14 and squid nerve vesicles (not shown here) it does not.…”
Section: Resultsmentioning
confidence: 75%
“…Many studies have shown that ATP increases the affinity of the transport sites for cytoplasmic Ca 2+ and extracellular Na + on squid axonal, optic lobe, and stellate ganglion Na + /Ca 2+ exchangers, and there is strong evidence that protein kinase activity may be involved in mediating these effects 10–12 . In previous studies, 13 the Na + /Ca 2+ exchanger from the adductor muscle of the bivalve mollusk, Placopecten magellanicus was found to be a substrate for PK‐A.…”
Section: Introductionmentioning
confidence: 98%